Monetary Policy Analysis in a Small Open Economy using Bayesian Cointegrated Structural VARs - Mattias Villani; Anders Warne (Sveriges Riksbank, 2003)
Structural VARs have been extensively used in empirical macroeconomics during the last two decades, particularly in analyses of monetary policy. Existing Bayesian procedures for structural VARs are at best confined to a severly limited handling of cointegration restrictions. This paper extends the Bayesian analysis of structural VARs to cover cointegrated processes with an arbitrary number of cointegrating relations and general linear restrictions on the cointegration space. A reference prior distribution with an optional small open economy effect is proposed and a Gibbs sampler is derived for a straight-forward evaluation of the posterior distribution. The methods are used to analyze the e.ects of monetary policy in Sweden.
Keywords: C11; C32; E52; 330; Structural; Vector autoregression; Monetary policy; Impulse responses; Counterfactual experiments